An armament as a sign of criminal organizations: the role of judicial ballistics at investigation of banditry - Костенко, М. В. (Theory and practice of jurisprudence, 2016)
The article dedicated to studying the role of the judicial ballistics in the investigation of crimes committed by criminal groups. The main idea of this study is the fact that armament is an inherent feature of banditry, which entails the need to study this phenomenon from the perspective of criminalistics namely judicial ballistics. Despite the diverse nature of the problem, namely the criminalistics emphasis of the topic is displayed in the article. Question the relevance of this subject is due to a rapidly developing of the arms market (including the «black market») and the impact of this development on the armed organized crime groups. Is a list of acts of national legislation of Ukraine that regulate legal relations connected with this phenomenon. Another problem of the research topic is the lack of the law «On Weapons» in the system national legislation of Ukraine, despite the presence of similar laws in foreign countries. Separately, emphasize the need to broaden the interpretation of the term «judicial ballistics» in connection with the enlarged list of subjects that fall under the study. The main part of the article is devoted to the description of new types of weapons that have appeared on the territory of Ukraine for the years of its independence, on their legal status and the possibility of using as weapons by organized criminal groups. Among these weapons are named: traumatic arms (pistols and revolvers), air arms (rifles) weapons chambered for «Flaubert» and the starting guns. In addition, the study points to the increasing role of the Internet in the commission of crimes today. Indicates that the weapon can be purchased by members of criminal gangs online. In this connection, attention is focused on the improvement of forensic technology in the industry of forensic identification device in the network, as well as precisely those members of organized criminal groups who commit crimes using via the Internet. At the end of the article there are four major conclusions regarding the studied issues. Firstly, there is a need to broaden the approach to the definition and understanding of the term «forensic ballistics». Secondly, it is the need to decide on technical and forensic level some issues related to criminalistics identification of and registration of new types of weapons. In continuation, points to the need to improve criminalistics technics in the industry of investigation crimes committed using the Internet. Moreover, it should take into account the need for appropriate changes in legislation. In conclusion, given the idea that the problems found and proposed their solutions do not solve the problem of organized crime, but will carry a minimum of a preventive nature.